Pengaruh Transparansi dan Akuntabilitas terhadap Pengelolaan Dana Desa dalam Mewujudkan Prinsip Good Governance - Meliani Fitrianti; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2024)
The main aim of this study was to investigate the impact of transparency and accountability on the effective management of village resources, within the framework of implementing principles of good governance. This research is a case study conducted as a case study in Padang Pariaman Regency. The study encompassed a total of 103 "nagari" (villages) in the regency, constituting 824 administrative units in total. The sampling method employed was simple random sampling. By using Slovin's formula to calculate the sample size, a total of 270 "nagari" units were selected as the sample. The research adopts a quantitative approach. Primary data for this study were collected through questionnaires distributed to village officials within Padang Pariaman Regency. Data analysis involved the utilization of linear regression techniques. The outcomes of this investigation reveal a positive and statistically significant correlation between transparency and accountability and the effective management of village funds.